2018
DOI: 10.3390/ijms19030723
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic Acid and Its Microbial Metabolites Exert Anti-Proliferative Effects, S-Phase Cell-Cycle Arrest and Apoptosis in Human Colon Cancer Caco-2 Cells

Abstract: Chlorogenic acid (CGA) decreases colon cancer-cell proliferation but the combined anti-cancer effects of CGA with its major colonic microbial metabolites, caffeic acid (CA), 3-phenylpropionic acid (3-PPA) and benzoic acid (BA), needs elucidation as they occur together in colonic digesta. Caco-2 cancer cells were treated for 24 h with the four compounds individually (50–1000 µM) and as an equimolar ratio (1:1:1:1; MIX). The effective concentration to decrease cell proliferation by 50% (EC50) was lower for MIX (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 36 publications
5
62
0
Order By: Relevance
“…Parallel with our antiproliferative results regarding Hydroxycitric Acid, it was observed the antiproliferative activity of citric acid in skin cancer by inducing apoptotic [31], and the antiproliferative activity of hydroxycitrate against lung cancer, bladder cancer, and melanoma [32]. Furthermore, it was reported that Chlorogenic Acid can inhibit the growth of colon cancer and leukemia by inducing cell cycle arrest at S-phase and activating caspase-3 [33].…”
Section: Discussionsupporting
confidence: 79%
“…Parallel with our antiproliferative results regarding Hydroxycitric Acid, it was observed the antiproliferative activity of citric acid in skin cancer by inducing apoptotic [31], and the antiproliferative activity of hydroxycitrate against lung cancer, bladder cancer, and melanoma [32]. Furthermore, it was reported that Chlorogenic Acid can inhibit the growth of colon cancer and leukemia by inducing cell cycle arrest at S-phase and activating caspase-3 [33].…”
Section: Discussionsupporting
confidence: 79%
“…This fact of metabolic activity reduction in many of the stressed but living promastigotes prompted us to assume that beyond leishmanicidal activity there must be additional effects of CGA to arrest the cell cycle of the promastigotes that ultimately resulted in decreased number of promastigotes in treated cultures. Recent reports from two different groups showed the efficacy of CGA to arrest cell cycle of colon cancer cells at S phase 27,28 . Our data for cell cycle analysis, as tracked after 36 hours treatment, showed significant higher accumulation of the CGA treated promastigotes in the G0/G1 phase than observed in untreated cells.…”
Section: Discussionsupporting
confidence: 53%
“…Numerous reports have shown that fresh fruits and vegetables have excellent antioxidant constituents and thus they may confer protection against chronic diseases caused by oxidative stress, such as cardiovascular disorders and some kinds of cancer [6][7][8][9][10]. Phenolic and flavonoid compounds have been reported to exhibit antioxidant properties [11].…”
Section: Introductionmentioning
confidence: 99%